Pengaruh Fintech Syariah Terhadap Inklusi Keuangan UMKM Melalui Platform Digital Microfinance - Deni Riani; Enur Hotimah (Fakultas Syariah IAIN Kerinci, 2026)
This study aims to examine the effect of Islamic fintech on MSME financial inclusion through the mediating role of the platform digital microfinance. A quantitative explanatory cross-sectional survey involved 120 MSME owners or managers in Trenggalek Regency selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling using SmartPLS. Islamic fintech had a positive and significant effect on MSME financial inclusion (β = 0.318; p = 0.001) and platform digital microfinance utilization (β = 0.734; p < 0.001). Platform utilization also positively affected financial inclusion (β = 0.547; p < 0.001) and significantly mediated the relationship between Islamic fintech and financial inclusion (indirect effect β = 0.401; p < 0.001), indicating partial mediation. The findings show that ease of use, security, contractual transparency, trust, and Sharia compliance can broaden MSMEs’ access to formal financial services. Regulators and financial service providers should strengthen digital infrastructure, financial literacy, data security, simplified financing procedures, and Sharia compliance supervision to support inclusive and sustainable financial services.